The Effect of Ice Breaking on Student Learning Concentration on the Subject of Islamic Religious Education - Lubis, Ayang Ratu Nita; Zuhri, Zuhri; Afriani, Gusma (Absorbent Mind, 2025)
This study aims to test the effect of ice breaking on children's learning concentration in Islamic Religious Education subjects at State Senior High School 10, Pekanbaru. This research method uses a quantitative approach and the Quasi-Experiment method with a Non-equivalent Control Group Design research design. The sample used in this study was 35 students of class X.1 as the experimental class and 35 students of class X.3 as the control class—sampling using a purposive sampling technique. Data collection was carried out using observation, questionnaires, and documentation. Data analysis techniques used parametric statistics, with the T-test. The results of this study indicate that there is a significant difference in student learning concentration between the control class and the experimental class in Islamic Religious Education subjects at State Senior High School 10 Pekanbaru, t_count is greater than t_table, which is 3.987> 1.667 and Sig. (2-tailed) = 0.000 < 0.05, then H_0 is rejected and H_a is accepted. It has been proven that ice-breaking affects students' concentration in learning.